Discrepancy between desired time in bed and desired total sleep time in patients with cancer: The DBST index and its relationship with insomnia severity and sleep onset latency - Cho, Eulah; Song, Jaeeun; Lee, Joohee; Cho, Inn-Kyu; Lee, Dongin; Choi, Hayun; Kim, Harin; Chung, Seockhoon (Frontiers in Psychiatry, 2023)
Patients with cancer experience insomnia or sleep disturbances. This study aimed to explore whether the discrepancy between a patient's desired time in bed and total sleep time (DBST) index can be used as a measurement tool for insomnia severity or sleep onset latency [SOL] in patients with cancer. This retrospective medical records review study gathered clinical information and scores from scales and indices such as the Insomnia Severity Index (ISI), Cancer-related Dysfunctional Beliefs about Sleep (C-DBS) scale, Patient Health Questionnaire-9 items (PHQ-9), State subcategory of State and Trait Anxiety Inventory, and the short form of the Fear of Progression Questionnaire. Sleep indices of time variables (bedtime, sleep onset time, and wake-up time), duration variables [SOL, time in bed (TIB), time in bed over 24 hours (TIB/d), and duration from wake-up time to bedtime (WTB)], and DBST index scores were calculated. ISI scores were predicted by the PHQ-9 (β = 0.34, P < 0.001), C-DBS scale (β = 0.17, P = 0.034), and DBST indices (β=0.22, P=0.004), with a significant correlation observed with the DBST index (r = 0.19, P =0.020). The DBST index was significantly correlated with long SOL values (r = 0.23, P = 0.005), and long SOL values were predicted by early bedtimes (β = 0.18, P = 0.045), short WTB durations (β = -0.26, P = 0.004), and high DBST index values (β = 0.19, P = 0.013). The DBST index was significantly correlated with predictive factors of both insomnia severity and SOL in patients with cancer.